Sosialisasi Dan Praktik Pengisian Buku Administrasi Bank Sampah “Sami Berkah” Kecamatan Tembalang Kota Semarang - Aniqotunnafiah; Endang Dwi Wahyuningsih; Kasidi; Nikmatul Hasanah; Ika Sabrina Luthfi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Abstract: Waste has become a serious threat to environmental sustainability and a contributing factor to global warming. Waste banks are a strategic solution to reduce the impact of waste generation by implementing the 3R principle (Reduce, Reuse, Recycle). This community service activity aims to improve the administrative and financial management capabilities of the